Activation of Hippocampal IR/IRS-1 Signaling Contributes to the Treatment with Zuogui Jiangtang Jieyu Decoction on the Diabetes-Related Depression. (4th June 2021) - Yang, Hui; Ling, Jia; Meng, Pan; Liu, Jian; Lin, Xiaoyuan; Li, Wei; Wang, Yuhong
Abstract : Background . Zuogui Jiangtang Jieyu decoction (ZJJ) is mainly used for the treatment of diabetes-related depression in current clinical applications and research. This study aims to investigate whether the brain IR/IRS-1 signaling pathway is involved in the therapeutic effect of ZJJ on depression-like behavior in diabetic rats. Methods . Sprague–Dawley rats were fed with high-fat diet and subjected to streptozotocin injection to establish the diabetes animal model. After treatment with different doses of ZJJ (20.530 g/kg or 10.265 g/kg) for 4 weeks, the blood glucose level and peripheral insulin resistance were measured. The forced-swimming test (FST) and Morris water maze test (MWMT) were applied for the mood and cognitive function assessment. Then, the Western blot method was used to analyze the protein levels of insulin receptor (IR), insulin receptor substrate-1 (IRS-1), phosphatidylonositol-3-kinase (PI3K), and protein kinase B (PKB, also as known as AKT) in the hippocampus of diabetic rats. Meanwhile, the immunofluorescence method was performed to analyze the above proteins' expression in the neuron and astrocyte. At last, the levels of glycogen, lactate, and ATP were tested by the ELISA method. Additionally, the insulin-sensitive glucose transporter 4 (GLUT4) and the lactate transporter monocarboxylate transporter 4 (MCT4) were analyzed by the Western blot method. Results . ZJJ administration significantly decreased the level of blood glucose and improved the peripheral insulin resistance in diabetic rats. Besides, ZJJ attenuated the depression-like behavior and the cognitive dysfunction in rats with diabetes. Furthermore, we found the upregulation of protein expression of phospho-IR, phospho-IRS-1, phospho-PI3K, and phospho-AKT in the hippocampus of diabetic rats after being treated with ZJJ. Moreover, the above proteins are increased not only in the neuron but also in the astrocyte after ZJJ administration. In addition, ZJJ increased the content of ATP, glycogen, and lactate, as well as the expression of GLUT4 and MCT4 in the hippocampus of diabetic rats. Conclusions . These findings suggest that ZJJ improves the depression-like behavior of diabetic rats by activating the IR/IRS-1 signaling pathway in both hippocampal neuron and astrocyte. And the brain IR/IRS-1 signaling pathway plays an important role in astrocyte-neuron metabolic coupling, providing a potential mechanism by which the IR/IRS-1 signaling pathway may contribute to the treatment of ZJJ on diabetes-related depression.